Simulating actuator energy consumption for trajectory optimisation. (September 2018) - Cooper, Michael; Lawson, Craig; Zare Shahneh, Amir
This work aims to construct a high-speed simulation tool which is used to quantify the dynamic actuator power consumption of an aircraft in flight, for use within trajectory optimisation packages. The purpose is to evaluate the energy penalties of the flight control actuation system as an aircraft manoeuvre along any arbitrary trajectory. The advantage is that the approximations include major transient properties which previous steady state techniques could not capture. The output can be used to provide feedback to a trajectory optimisation process to help it compute the aircraft level optimality of any given flight path. The tool features a six degree of freedom dynamic model of an aircraft which is combined with low frequency functional electro-mechanical actuator models in order to estimate the major transient power demands. The actuator models interact with the aircraft using an aerodynamic load estimator which generates load forces on the actuators that vary as a function of flight condition and control surface demands. A total energy control system is applied for longitudinal control and a total heading control system is implemented to manage the lateral motion. The outer loop is closed using a simple waypoint following guidance system with turn anticipation and variable turn radius control. To test the model, a simple trajectory analysis is undertaken which quantifies a heading change executed with four different turn rates. The tool shows that the actuation system requires 12.8 times more electrical energy when performing a 90° turn with a radius of 400 m compared to 1000 m. A second test is performed to verify the model's ability to track a longer trajectory under windy conditions.